1995
DOI: 10.1007/bf01309722
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the long terminal repeat of feline immunodeficiency viruses from Japan, Argentina and Australia

Abstract: The nucleotide sequences of the long terminal repeat of five Japanese, five Argentine and three Australian isolates of feline immunodeficiency virus (FIV) were determined and compared with those of isolates previously described. The results revealed that the Japanese isolates were found to cluster with nucleotide sequence similarity of 95.6%-99.4%. The Australian isolates also clustered with nucleotide sequence similarity of 97.2%-99.4%. The Argentine isolates formed two groups; the LP9 isolate is closely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In a related paper, Yamada et al (1995) described similar results in the phylogenetic analysis of nucleotide sequences of FIV long terminal repeats and found that LP9 clustered together with subtype B sequences, whereas LP3, LP20 and LP24 formed a new group, Although there are no reports on significant biological differences among the five subtypes, the analyses presented here suggested that in the design of an FIV candidate vaccine, subtypes might have to be taken into consideration.…”
supporting
confidence: 54%
“…In a related paper, Yamada et al (1995) described similar results in the phylogenetic analysis of nucleotide sequences of FIV long terminal repeats and found that LP9 clustered together with subtype B sequences, whereas LP3, LP20 and LP24 formed a new group, Although there are no reports on significant biological differences among the five subtypes, the analyses presented here suggested that in the design of an FIV candidate vaccine, subtypes might have to be taken into consideration.…”
supporting
confidence: 54%
“…Alternatively, the primers used in these experiments may not necessarily detect all the FIV types and subtypes, due to the relatively high intrinsic mutation rates of gag, pol and env genes in lentivirus (Greene et al, 1993). A phylogenetic analysis based on the nucleotide sequences of LTR (long terminal repeat) regions of the genome of the virus, demonstrated the existence of four groups (Sodora et al, 1994;Kakinuma et al, 1995;Yamada et al, 1995) including the Argentinean subtype which is quite distant from other reported isolates and forms a new FIV group (Pecoraro et al, 1996). However, for the majority of the groups little sequence data are available (Uema et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A DNase I footprinting assay using nuclear protein extracts from a feline T-lymphoma cell line revealed specific nuclear proteinbinding to the putative AP-1, ATF and C\EBP sites (Thompson et al, 1994). Previously, we and others demonstrated genetic diversity in the LTR among FIV isolates (Thompson et al, 1994 ;Yamada et al, 1995). Although cross-competition between putative AP-1 and ATF motifs of FIV UK8 strain was suggested (Thompson et al, 1994), it is still not known whether there are differences in the proteins that bind to the putative AP-1 or ATF site among different FIV isolates or different cell types.…”
mentioning
confidence: 99%